(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article investigates the role of the case study approach in teaching English as a Foreign Language (EFL). It evaluates the pedagogical strengths of the method, particularly its ability to encourage critical thinking, real-world language application, and collaborative learning. By examining relevant theoretical frameworks and practical examples, the article demonstrates how the case study method can promote the development of both linguistic and intercultural competence in students. The article also explores the challenges that teachers face when implementing case studies in language classrooms and provides suggestions for overcoming these barriers.